2016
DOI: 10.3389/fbioe.2016.00062
|View full text |Cite
|
Sign up to set email alerts
|

How Biomaterials Can Influence Various Cell Types in the Repair and Regeneration of the Heart after Myocardial Infarction

Abstract: The healthy heart comprises many different cell types that work together to preserve optimal function. However, in a diseased heart the function of one or more cell types is compromised which can lead to many adverse events, one of which is myocardial infarction (MI). Immediately after MI, the cardiac environment is characterized by excessive cardiomyocyte death and inflammatory signals leading to the recruitment of macrophages to clear the debris. Proliferating fibroblasts then invade, and a collagenous scar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 141 publications
0
12
0
Order By: Relevance
“…Biomaterial therapy with or without growth factors may aid myocardial repair by providing mechanical support to the heart tissue, and affecting tissue inflammation and angiogenesis 17 26 . However, the efficacy remains low due to their inability to provide oxygen to metabolic-demanding cardiac cells at early stage of tissue damage 15 , 16 . To address the critical need of oxygen to protect cardiac cells, direct supply of sufficient oxygen in the infarcted area while not provoking deleterious effects is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterial therapy with or without growth factors may aid myocardial repair by providing mechanical support to the heart tissue, and affecting tissue inflammation and angiogenesis 17 26 . However, the efficacy remains low due to their inability to provide oxygen to metabolic-demanding cardiac cells at early stage of tissue damage 15 , 16 . To address the critical need of oxygen to protect cardiac cells, direct supply of sufficient oxygen in the infarcted area while not provoking deleterious effects is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of hydrogel administration include direct mechanical strengthening [ 36 ], enhanced angiogenesis and regeneration of myocardial tissue, reduced apoptosis and scar size, and improved cardiac function recovery [ 37 ]. Moreover, multiple studies showed that the use of biomaterials alone favorably affects various cells in the post-MI environment such as macrophages, cardiomyocytes, fibroblasts, and endothelial cells [ 38 ]. Recently, hydrogels made of ECM-based biomaterials have drawn attention because of their ability to mimic native ECM and minimize immunogenicity [ 39 ].…”
Section: Biomaterials Loaded With Growth Factors and Cytokines Formentioning
confidence: 99%
“…Downstream signaling proceeds via RAS-mitogen-activated protein kinase RAS-(MAPK) and phosphatidylinositide 3-kinase (PI3K) pathways [ 55 ]. In a separate study, sustained and targeted delivery of neuregulin-1β (NRG), which is a member of epidermal growth factor that regulates cardiomyocyte development and proliferation, by a hydroxyethyl methacrylate hyaluronic acid (HEMA-HA) hydrogel, demonstrated a cardioprotective effect and significantly improved ventricular function and structure [ 38 ]. The cardioprotective effect was assessed by the amount of caspase-3 in murine hearts post-MI, which was significantly reduced in the NRG-hydrogel group in comparison to the control groups treated with phosphate-buffered saline, NRG, or hydrogel alone.…”
Section: Biomaterials Loaded With Growth Factors and Cytokines Formentioning
confidence: 99%
“…MI involves the pathogenesis of anaerobic respiration, the accumulation of reactive oxygen species, and the death of cardiomyocytes (CM), thus affecting the normal physiological process of the heart [ 5 ]. Post myocardial infarction, the CM extracellular matrix (ECM) undergoes inflammatory, proliferation, and maturation stages of tissue remodeling to support other healthy CM [ 6 , 7 ]. However, the scar tissue or collagen formed by the remodeling of the ECM at the maturation stage does not participate in the concomitant beating of the heart due to loss of organized architecture [ 8 ], which eventually leads to cardiomegaly and, ultimately, heart failure [ 6 ].…”
Section: Biomaterials For Cardiac Regenerationmentioning
confidence: 99%
“…Post myocardial infarction, the CM extracellular matrix (ECM) undergoes inflammatory, proliferation, and maturation stages of tissue remodeling to support other healthy CM [ 6 , 7 ]. However, the scar tissue or collagen formed by the remodeling of the ECM at the maturation stage does not participate in the concomitant beating of the heart due to loss of organized architecture [ 8 ], which eventually leads to cardiomegaly and, ultimately, heart failure [ 6 ]. Present-day remedies like surgical, pharmacological, and endovascular interventions only have soothing purposes and do not address the fundamental flaw, which is the loss of functional CM [ 9 ].…”
Section: Biomaterials For Cardiac Regenerationmentioning
confidence: 99%